Orientation on Moderate Religion Ffr StudentsFaculty of Tarbiyah, IAIN Parepare - Mukhtar Mas’ud (Journal of Pedagogi, 2026)
The implementation of religious moderation is a process aimed at fostering religious moderation among students of the Faculty of Tarbiyah at IAIN Parepare. There are many things students can learn to equip them to behave appropriately and courteously towards followers of other religions, whether fellow believers or adherents of different faiths. This is particularly important once they have attained a Bachelor‘s degree, as they should possess not only academic knowledge but also an understanding of religious moderation. The scope of religious moderation is humanity (humanity), namely treating people with humanity so that harmonious interactions with fellow human beings may take place. The public interest (public interest) is the endeavour to safeguard public facilities and matters that benefit others, ensuring they are preserved and can be utilised in the long term. Justice (justice) is a fair attitude towards others when making decisions, including regarding regulations within a country. Balance (balance) means not favouring any particular person or group, so that everyone is treated equally. Constitutionalism is the duty of every citizen to comply with the law, as well as government statutes and regulations. National commitment (national commitment) is the commitment of citizens to love their homeland and possess a sense of national identity. Tolerance is a commendable attitude of granting others the freedom to practise their religion according to their beliefs. Non-violence is an attitude and behaviour whereby a person avoids violence to maintain peace within society. It is hoped that students of the Faculty of Tarbiyah at IAIN Parepare will put religious moderation into practice, both towards their fellow students and towards the lecturers who teach and mentor them, as well as towards other members of the academic staff. And after graduating, they are obliged to apply this to the wider community, both to fellow members of their own faith and to followers of other religions, by properly maintaining harmony, tolerance and peace so that constructive social interaction is realised and no social or religious problems arise within society. If this is successfully implemented, it means that the lecturers who have guided the students regarding religious moderation can be said to have succeeded. This success is, of course, inseparable from the efforts of the lecturers in dedicating their time, thought and ideas so that the knowledge and implementation of religious moderation can be of practical use to these students. The implications of religious orientation for students at the Faculty of Tarbiyah, IAIN Parepare, include: a) A reduction in mistrust amongst students due to mutual respect for differing opinions; b) The absence or reduction of radical actions as they better understand the harm caused by such actions; c) A reduction in fanaticism and extremism as they have come to understand the importance of maintaining balance and moderation; d) A reduction in disputes over differences in religious schools of thought amongst students as they have come to believe that a school of thought is part of an individual‘s faith to be practised, and that such differences must be respected; e) possessing knowledge of religious moderation, which serves as a foundation when implemented within society.